Crowning Glories Netherlandish Realism and the French Imagination during the Reign of Louis XIV - Stone, Harriet 1953- (University of Toronto Press, 2019)
Examining cultural production during the reign of Louis XIV, Crowning Glories brings together the role of the arts in the monarchy's propaganda wars, the significance of Netherlandish realism in France, and the rise of empiricism in the early modern period.